Theory Fundamentals Workbook - Yang, Gregory (Open textbook library., 2023)
This workbook is a practical method for learning the rudiments of music, which are essential to a thorough understanding of music in general. Designed as a supplement to professional instruction rather than a manual for self instruction, the text is intentionally brief. The emphasis is on using practical exercises to develop fluency. Aural, vocal, and keyboard skills must be integrated into the study of music theory from the very beginning. I encourage all students, regardless of their principal instrument, to learn to hear, sing, and play on the piano everything that they do in theory. All exercises in this book should be completed thoroughly. Usually a sample will be completed in brackets for each exercise, as a demonstration. Fluency with these basic materials of music will be a great asset to any further musical endeavors. For students who need additional exercises, suggestions for further study will be given.